The influence of ethnic culture orientation on SME performance in Indonesia: The mediating role of resource orchestration capability as a strategic tool - Muhammad Basyir; Faisal; Mahdani Ibrahim; Mirza Tabrani (Problems and Perspectives in Management, 2025)
This study aims to examine how ethnic culture orientation influences the performance of small and medium enterprises (SMEs) in Western Indonesia, particularly through the mediating role of resource orchestration capability as a strategic management tool. The analysis involved 232 SME owners and managers operating in food processing, handicrafts, and traditional textiles, i.e., industries known for their strong cultural foundations. Respondents were selected using purposive sampling to ensure they had embedded ethnic culture values in their business practices. Data collection was conducted from June to August 2024 using structured questionnaires distributed via Google Forms and WhatsApp. The data were analyzed using structural equation modeling (SEM) with AMOS. Results show that ethnic culture orientation significantly affects both resource orchestration capability (β = 0.336; p = 0.002) and SME’s performance (β = 0.213; p = 0.012), while resource orchestration capability has a strong impact on SME’s performance (β = 0.785; p < 0.001). Mediation analysis reveals that resource orchestration capability fully mediates the relationship between ethnic culture orientation and SME’s performance, as the indirect effect is significant (p < 0.001), and the direct effect becomes insignificant. These findings underscore the importance of developing strategic capabilities that align with cultural values to improve SME’s performance in culturally rich regions.